Neighboring genes shaping a single adaptive mimetic trait (2014)
The colorful wing patterns of Heliconius butterflies represent an excellent system in which to study the genetic and developmental control of adaptation and convergence. Using qRT?PCR and in situ hybridization on developing wings of the co?mimic species Heliconius melpomene and Heliconius erato , we have profiled the expression of three candidate genes located in the genomic locus controlling red color pattern variation. We found convergent domains of gene expression in H. melpomene and H. erato associated with red wing elements in the two genes optix and kinesin . During early pupal development of both species, the expression of optix perfectly associated with all red pattern elements whereas that of kinesin was specifically correlated with the presence of the red forewing band. These results provide evidence for the use of these two tightly linked patterning genes, acting together to create convergent wing phenotypes in Heliconius and constituting a hotspot of adaptation.